Pregnancy Outcome of Multiparous Women Aged over 40 Years - Ates, Seda; Batmaz, Gonca; Sevket, Osman; Molla, Taner; Dane, Cem; Dane, Banu (International Journal of Reproductive Medicine, 2013)
Objective. The aim of this study was to evaluate the effect of maternal age on prenatal and obstetric outcome in multiparaous women. Materials and Methods. A retrospective case control study was conducted, including women aged 40 years and over (study group, n=97) who delivered at 20 week’s gestation or beyond and women aged 20–29 years (control group, n=97). Results. The mean age of women in the study group was 41.2±1.7 years versus 25.4±2.3 years in the control group. Advanced maternal age was associated with a significantly higher rate of hypertension, diabetes mellitus, fetal complication, and 5-minute Apgar scores <7 (P<0.05). Caeserean section rate, incidence of placental abruption, preterm delivery, and neonatal intensive care unit admission were more common in the older group, but the differences were not statistically significant. Conclusions. Advanced maternal age is related to maternal and neonatal complications.